1998
DOI: 10.1021/jp9824095
|View full text |Cite
|
Sign up to set email alerts
|

Resonance Raman and FTIR Studies of Carbon Monoxide-Bound Cytochrome aa3-600 Oxidase of Bacillus subtilis

Abstract: Resonance Raman and FTIR spectra are reported for the fully reduced carbon monoxy derivative of the quinol aa 3-600 oxidase from Bacillus subtilis. The resonance Raman spectra display two isotope-dependent vibrational modes at 520 and 575 cm-1. The FTIR spectrum displays a single vibrational mode at 1963 cm-1. We assign the band at 520 cm-1 to the Fe−CO stretching mode, the band at 575 cm-1 to the Fe−C−O bending mode, and the band at 1963 cm-1 to the C−O stretching mode. The frequencies of these modes are sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
28
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 38 publications
7
28
0
Order By: Relevance
“…This way, the optical transition will shift to higher energy as a result of the increased splitting of the d orbitals and the energy of the antibonding * orbitals. The data for the aa 3 -type oxidase from Bacillus subtilis (55) show that such heme-linked ionization phenomena exist in heme copper oxidases, which also occur for the peroxidase class of enzymes (56), and are consistent with our interpretation that the effect that comes from the unique interactions between the oxoferryl species and the distal heme pocket environment. Thus, the formation of the 607-nm species can communicate events to the proximal environment, causing perturbations in the H-bonding interactions of His-411.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This way, the optical transition will shift to higher energy as a result of the increased splitting of the d orbitals and the energy of the antibonding * orbitals. The data for the aa 3 -type oxidase from Bacillus subtilis (55) show that such heme-linked ionization phenomena exist in heme copper oxidases, which also occur for the peroxidase class of enzymes (56), and are consistent with our interpretation that the effect that comes from the unique interactions between the oxoferryl species and the distal heme pocket environment. Thus, the formation of the 607-nm species can communicate events to the proximal environment, causing perturbations in the H-bonding interactions of His-411.…”
Section: Discussionsupporting
confidence: 88%
“…This interpretation finds support from earlier RR studies in which it has been shown that the properties of the trans ligand of oxoferryl complexes can affect the bonding between the iron and the oxygen, and thus, can affect its vibrational frequency (68); the vibrational frequency decreases as the ligand becomes more electron-donating to Fe(IV)ϭO. Along these lines, a high Fe-His mode arises from a population in which the hydrogen bond is intact, whereas a lower frequency of the Fe-His vibration reflects a form of the enzyme lacking the hydrogen bond (55). Based on the crystal structure, the proximal His-411 is capable of forming a hydrogen bond with Gly-378, and thus, the H-/non H-bonding interaction of the proximal His-411 with Gly-378 is the most likely contributor to the vibrational differences between the two oxoferryl species.…”
Section: Discussionmentioning
confidence: 99%
“…We assign the peaks at 1967, 1973, and 1982 cm Ϫ1 to the C-O stretching modes of heme a 3 -CO (complex B), and the peak at 2053 cm Ϫ1 to the C-O stretching mode of Cu B 1ϩ -CO (complex A). The mode at 1967 cm Ϫ1 is similar to that found for the ␣-form in the CO adducts of aa 3 oxidases from bovine heart, Rhodobacter sphaeroides, aa 3 -600, and P. denitrificans (21)(22)(23)(24)(25)(26)(27)(28), and the 1973 cm Ϫ1 mode is 2 cm Ϫ1 lower than the ␥-form found in P. denitrificans (28). The frequency of the 1982 cm Ϫ1 mode, however, does not coincide with the ␤-form found in other heme-copper oxidases (20 -23), and thus, we suggest that it represents a structure of the active site in which Cu B exerts a strong steric effect on the heme a 3 -bound CO.…”
Section: Resultssupporting
confidence: 70%
“…Information concerning the active site of heme-copper oxidases has been deduced from resonance Raman studies of the CO-bound form of the enzymes (22,24,28,34). In one of these studies, Rousseau and co-workers (34), based upon pH dependent changes seen in the heme a 3 Fe-CO stretching frequency, proposed that structural changes that modulate the position of Cu B with respect to the heme-CO are coupled to protonation/ deprotonation events of one or more residues.…”
Section: Discussionmentioning
confidence: 99%
“…Resonance Raman spectra were obtained from 40 -50 M samples, pH 7.5, in a cylindrical quartz spinning cell. The RR data were acquired as described elsewhere (10,11,13). FTIR spectra were recorded from 400 M samples at 4 cm Ϫ1 resolution with a Bruker Equinox 55 FTIR spectrometer equipped with a liquid nitrogen cooled mercury cadmium telluride detector.…”
Section: Methodsmentioning
confidence: 99%